Short stature and hypoparathyroidism in a child with Kenny-Caffey syndrome type 2 due to a novel mutation in FAM111A gene. (December 2017) - Abraham, Mary; Li, Dong; Tang, Dave; O'Connell, Susan; McKenzie, Fiona; Lim, Ee; Hakonarson, Hakon; Levine, Michael; Choong, Catherine
Abstract Background Hypoparathyroidism in children is a heterogeneous group with diverse genetic etiologies. To aid clinicians in the investigation and management of children with hypoparathyroidism, we describe the phenotype of a 6-year-old child with hypoparathyroidism and short stature diagnosed with Kenny-Caffey syndrome (KCS) Type 2 and the subsequent response to growth hormone (GH) treatment. Case presentation The proband presented in the neonatal period with hypocalcemic seizures secondary to hypoparathyroidism. Her phenotype included small hands and feet, hypoplastic and dystrophic nails, hypoplastic mid-face and macrocrania. Postnatal growth was delayed but neurodevelopment was normal. A skeletal survey at 2 years of age was suggestive of KCS Type 2 and genetic testing revealed a novelde novo heterozygous mutation c.1622C > A (p.Ser541Tyr) inFAM111A . At 3 years and 2 months, her height was 80cms (SDS −3.86). She had normal overnight GH levels. GH therapy was commenced at a dose of 4.9 mg/m2 /week for her short stature and low height velocity of 5cms/year. At the end of the first and second years of GH treatment, height velocity was 6.5cms/year and 7.2cms/year, respectively with maximal dose of 7.24 mg/m2 /week. Conclusion This case highlights the phenotype and the limited response to GH in a child with genetically proven KCS type 2. Long-term registries monitoring growth outcomes following GH therapy in patients with rare genetic conditions may help guide clinical decisions regarding the use and doses of GH in these conditions.